Descriptive and approximate translation of Arabic & Russian creative texts: Individual approaches to practical adaptation with text - Al-Safi, Bayan Maqsed (Journal of Humanities & Social Sciences, 2021)
The aim of the study is to provide insights to the new generation of translators on the importance of using the descriptive and approximate method and the use of the individual method to adapt to the secular and sacred creative texts to avoid the mistakes of their predecessors. The study highlights the need to modernize education and training in the field of creative translation. The research discusses the concept of linguistic equivalence، which constitutes a major problem in theorizing the science of translation and in the creative translation process، especially in poetic texts and in sacred texts، due to the presence of context، melody and poetic taste in poetic texts and the presence of rhetorical and semantic differences in the sacred texts. The research deals with the importance of studying the structure of the two languages and knowing the analysis of the syntax in the translation process، as well as the importance of dissecting the linguistic structure of each language، taking into account the multiplicity of meanings in one word، and also the importance of translating the text from its original language، due to the difficulties of delving deep into the words without knowledge of the original language، and the psychological، cultural and environmental factors of the creator of the original text، which constitutes an effective element to determine the success rate of the translator’s work.